Tuberculosis: The implications for anaesthesia - T.A. Jackson; J.M. Thomas (South African Family Practice, 2014)
Tuberculosis is a common problem in South Africa, and provides a number of challenges for the anaesthetist. Patients may present in a variety of ways. Constitutional and pulmonary symptoms are the most common. These may impact on fitness for surgery and choice of anaesthesia. Tuberculosis treatment has the potential for a number of significant drug interactions. These are primarily mediated through induction of the cytochrome P450 enzyme system by rifampicin. Guidelines for the prevention of tuberculosis in the theatre environment need to be followed to avoid placing staff and other patients in danger.